Comparison of Mikalojus Daukša’s „Catechism“ (1595) and Its Polish Original: Onomateme „širdis“ and Its Equivalents - Pajėdienė, Jūratė (Vilnius University Open Series, 2021)
The article continues the research, which centers on the comparison of Mikalojus Daukša’s Catechism (DK, 1595) and its Polish original – Jakub Ledesma’s Catechism (LeK, ~1572). This time the article focuses on the polysemy of the word širdis, which becomes apparent in the comparison of the fixations of this word in Daukša’s texts (Daukša’s Postilla (DP, 1599) is referred to as an additional source) and their original Polish equivalents as well as the contexts of their usage. DK lexeme širdis corresponds to LeK serce, serdeczny, żywot, myśl, vmysł. DP lexeme širdis is selected as an equivalent to the lexemes and phrases with serce, serdeczny, myśl, vmysł, męstwo, pamięć, sumnienie, stałość, trwałość, żalość, wdziecżnie, miec na pieczy in Jakub Wujek’s text. The inconsistencies between the onomateme širdis and the Polish original are due to the translation author’s creative experience as well as the range of meanings associated with this word and its phrases in the native language and the tradition of usage.
Keywords: Mikalojus Daukša’s Catechism; translation; inconsistencies in translation; the polysemy of the word širdis; formula of the confession of sins